Meningkatkan Kualitas Manajemen Lembaga Pendidikan Islam Melalui Sumber Daya Manusia di Era Pandemi - Syamsul Bahri (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
The goal of this paper is to discover the obstacles that prohibit Islamic educational institutions from improving the quality of their human resources and how to overcome them. Data was gathered and analyzed from a variety of sources, including novels and scholarly papers. This qualitative approach was carried out using descriptive and argumentative analysis. The study's findings show that improving the quality of human resources in Islamic educational institutions includes developing and improving the evaluation system, improving educational facilities, developing and procuring teaching materials, and training teachers and education personnel in order to achieve the government's goals, vision, and mission. Following up on the findings of this study, one of the issues that Islamic educational institutions must address is the production of dedicated and committed people resources who comprehend science and technology. To address these demands, Islamic educational institutions must refresh their roles in order to play an ideal role in attaining academic excellence, industrial relevance, new knowledge contribution, and empowerment.